2017
DOI: 10.1080/13561820.2016.1272559
|View full text |Cite
|
Sign up to set email alerts
|

Exploring stakeholder experiences of interprofessional teamwork in sex development outpatient clinics

Abstract: Adopting an interprofessional team approach to care of the child with rare conditions that can affect sex development (DSD) has been advocated by a consensus document within the last decade. In the United Kingdom, the approach appears orientated towards an interprofessional model with the integration of separate professions working in single consultations with families working collaboratively to focus on care using a person and family-centred lens. This concurrent mixed-methods UK study using questionnaires, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 44 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…Out of the final 12 articles, 6 were theoretical, [11][12][13][14][15][16] 5 were empirical [17][18][19][20][21] and 1 was a mixed-method study. 9 Onethird (4) of the articles were published in the UK, 9 11 12 18 the other third in the USA 13 15 17 20 and the remaining third came from Switzerland and Germany, 21 Sweden and UK, 19 Australia 16 and Germany 14 (see tables 2 and 3).…”
Section: General Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the final 12 articles, 6 were theoretical, [11][12][13][14][15][16] 5 were empirical [17][18][19][20][21] and 1 was a mixed-method study. 9 Onethird (4) of the articles were published in the UK, 9 11 12 18 the other third in the USA 13 15 17 20 and the remaining third came from Switzerland and Germany, 21 Sweden and UK, 19 Australia 16 and Germany 14 (see tables 2 and 3).…”
Section: General Characteristics Of Included Studiesmentioning
confidence: 99%
“…Still most of the papers seemed to indicate a multidisciplinary approach in MDTs described as the simultaneous but independent contribution of two or more team members. Two empirical studies 19 21 and the mixed-methods study 9 show that although participants referred to their team as an MDT or even interprofessional, their responses reflect a disintegrated approach.…”
Section: Models Of Collaboration and Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed an interview guide based on research questions, clinical experiences, and literature review (Appendix A) [10][11][12][13]. The guide was used to initiate the interview and stimulate discussion.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, further methodological considerations pertain to the approach and goal(s) of individual evaluations, including attention to a patient's particular needs and the patienthealthcare professional relationship. For example, a study looking at stakeholder experiences of interprofessional teamwork in DSD revealed that consistency among team members and review with professionals known to the family was described as very helpful in coping with clinical aspects of DSD [Sanders et al, 2017].…”
Section: Psychological Evaluation Of Individuals For Clinical Managementmentioning
confidence: 99%